2013
DOI: 10.1111/1467-9566.12094
|View full text |Cite
|
Sign up to set email alerts
|

Careful science? Bodywork and care practices in randomised clinical trials

Abstract: Concern about obesity has prompted numerous public health campaigns that urge people to be more physically active. The campaigns often include normative statements and attempt to impose restrictions on individuals' lives without considering the complexities of daily life. We suggest that broadening the focus to reflect everyday practices would foster better targeted public health campaigns. This article is based on our participation in FINE, a multidisciplinary Danish research project. The core methodology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…In the trial sites participants found friendly and professional physician-investigators who had the opportunity and were willing to select and monitor their treatment regimens, provide consultations and be reachable in case of problems and emergencies during and after trials. Continuous relations with and the attention of physician-investigators were the main benefits of trial enrollment for interviewed participants, which in line with other studies highlights the central importance of personal and relational work in constructing research and treatment interface (Jespersen et al, 2013;Easter et al, 2006). Many of them considered these benefits to be life-saving (as one participant conveyed: 'I was prognosed to live for 1 year, but here I am alive for 21 years, all because I got here' (participant, site 3).…”
Section: Discussionsupporting
confidence: 87%
“…In the trial sites participants found friendly and professional physician-investigators who had the opportunity and were willing to select and monitor their treatment regimens, provide consultations and be reachable in case of problems and emergencies during and after trials. Continuous relations with and the attention of physician-investigators were the main benefits of trial enrollment for interviewed participants, which in line with other studies highlights the central importance of personal and relational work in constructing research and treatment interface (Jespersen et al, 2013;Easter et al, 2006). Many of them considered these benefits to be life-saving (as one participant conveyed: 'I was prognosed to live for 1 year, but here I am alive for 21 years, all because I got here' (participant, site 3).…”
Section: Discussionsupporting
confidence: 87%
“…Bodies that interact and share loads of work and perform physical activity in choreographed, interdependent actions (Jespersen et al . ).…”
Section: Collective Time and Bodiesmentioning
confidence: 97%
“…In the everyday efforts of the households to live up to ideals and maintain balance within the household, the dynamics and tensions between practices require alignment, coordination and choreography (Jespersen et al . , Lassen et al . ).…”
Section: Conceptualising Householdsmentioning
confidence: 99%
See 1 more Smart Citation
“…); as a technique of control of less cooperative bodies (Jespersen et al . ); and the ways in which the interaction varies by organisational context (Kerr ). We therefore suggest that it is useful to consider this relationship further, in specific relation to the management of emotion in the body work of abortion, and the ways in which this emotional labour is constrained by the organisational context of the hospital/clinic.…”
Section: Body Workmentioning
confidence: 99%